The mediating effect of cognitive and emotional processing on PTSD and depression symptoms reduction in women victims of IPV - Procaccia, Rossella; Castiglioni, Marco (Frontiers in Psychology, 2022)
Intimate partner violence (IPV) is a serious social, medical, and mental health concern. Women victims of IPV are at greater risk of experiencing severe psychological distress, such as depression and PTSD. In addition to standard psychotherapy, an adjuvant intervention that recently received considerable attention is expressive writing (EW) about trauma. Research has begun to explore the underlying cognitive and emotional processes associated with health improvements in trauma narratives. This study aims to evaluate the change in PTSD and depression symptoms after EW and examine the mediating effect of emotional and cognitive processing on symptom reduction in the EW group. Seventy-seven abused women (mean age=41,43 SD=10,75) were randomly assigned to a three-session expressive writing (n. 43) and neutral writing conditions (n=34). Psychological distress (PTSD and depression symptoms) was assessed before and after writing sessions. Through LIWC, narratives regarding emotional processing (positive and negative emotions) and cognitive processing (insight and causal references) were analyzed. The mediation model indicated that the reduction of depression was totally mediated by negative emotion processing and partially mediated by cognitive processing, while the reduction of PTSD is partially mediated by negative emotion processing and totally mediated by cognitive processing. No effect of positive emotion processing was found. Clinical implications are discussed.